Anti-PD-1 Therapy in SUFU mutant Patients with Gorlin-Goltz Syndrome - Moreira, Alvaro; Kirchberger, M. C.; Toussaint, Frédéric; Erdmann, M.; Schuler, Gerold; Heinzerling, Lucie (2018)
EVALuna2:34776

Blood eosinophilia is an on-treatment biomarker in patients undergoing vaccination with dendritic cells that correlates with long-term patient outcome - Moreira, Alvaro; Vass, V.; Erdmann, M.; Sponagl, F.; Schuler, Gerold; Schuler-Thurner, Beatrice (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-09-13

Blood eosinophilia is an on-treatment biomarker in patients with solid tumors undergoing dendritic cell vaccination with autologous tumor-RNA - Moreira, Alvaro; Erdmann, Michael; Uslu, Ugur; Vass, Verona; Schuler, Gerold; Schuler-Thurner, Beatrice (Pharmaceutics, 2020)
Background: The approvals of immune checkpoint inhibitors for several cancer types and the rapidly growing recognition that T cell-based immunotherapy significantly improves outcomes for cancer patients led to a re-emergence of cancer vaccines, including dendritic cell (DC)-based immunotherapy. Blood and tissue biomarkers to identify responders and long-term survivors and to optimize cost and cost-effectiveness of treatment are greatly needed. We wanted to investigate whether blood eosinophilia is a predictive biomarker for patients with solid tumors receiving vaccinations with DCs loaded with autologous tumor-RNA. Methods: In total, 67 patients with metastatic solid tumors, who we treated with autologous monocyte-derived DCs transfected with total tumor mRNA, were serially analyzed for eosinophil counts and survival over the course of up to 14 years. Eosinophilic counts were performed on peripheral blood smears. Results: Up to 87% of the patients treated with DC-based immunotherapy experienced at least once an eosinophilia of ≥ 5% after initiation of therapy; 61 % reached levels of ≥ 10% eosinophils, and 13% of patients showed eosinophil counts of 20% or above. While prevaccination eosinophil levels were not associated with survival, patients with blood eosinophilia at any point after initiation of DC-based immunotherapy showed a trend towards longer survival. There was a statistically significant difference for the patients with eosinophil counts of 20% or more (p = 0.03). In those patients, survival was prolonged to a median of 58 months (range 2-111 months), compared to a median of 20 months (range 0-119 months) in patients with lower eosinophil counts. In 12% of the patients, an immediate increase in eosinophil count of at least 10 percentage points could be detected after the first vaccine, which also appeared to correlate with survival (65 vs. 24 months; p = 0.06). Conclusion: Blood eosinophilia appears to be an early, on-therapy biomarker in patients with solid tumors undergoing vaccination with RNA-transfected DC, specifically autologous tumor mRNA-transfected DC vaccines, and it correlates with long-term patient outcome. Eosinophilia should be systematically investigated in future trials.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Biomarkers; Dendritic cell vaccines; Eosinophils

Characterization of Patients with inoperable malignant Stage IIIB-D Melanoma - Zaremba, A.; Weishaupt, C.; Glutsch, V.; Schilling, B.; Loquai, C.; Rafei-Shamsabadi, D.; Meiss, F.; Gutzmer, R.; Haferkamp, S.; Kaehler, K.; Moreira, Alvaro; Heinzerling, Lucie; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-09-13

Checkpoint inhibitor-induced eosinophilic fasciitis following high eosinophilia associated with complete response - Toussaint, Frédéric; Hammon, Matthias; Erdmann, Michael; Moreira, Alvaro; Kirchberger, Michael C.; Schuler, Gerold; Schett, Georg; Heinzerling, Lucie (Rheumatology, 2019)
CRIS-Team Scopus Importer:2019-10-01

Clinical characteristics and therapy response in unresectable melanoma patients stage IIIB-IIID with in-transit and satellite metastases - Zaremba, Anne; Philip, Manuel; Hassel, Jessica C.; Glutsch, Valerie; Fiocco, Zeno; Loquai, Carmen; Rafei-Shamsabadi, David; Gutzmer, Ralf; Utikal, Jochen; Haferkamp, Sebastian; Reinhardt, Lydia; Kähler, Katharina C.; et al. (European Journal of Cancer, 2021)
Introduction: Cutaneous melanoma is notorious for the development of in-transit metastases (ITM). For unknown biological reasons, ITM remain the leading tumour manifestation without progression to distant sites in some patients. Methods: In total, 191 patients with initially unresectable stage III ITM and satellite metastases from 16 skin cancer centres were retrospectively evaluated for their tumour characteristics, survival and therapy response. Three groups according to disease kinetics (no distant progress, slow (>6 months) and fast (<6 months) distant progression) were analysed separately. Results: Median follow-up time was 30.5 (range 0.8–154.0) months from unresectable ITM. Progression to stage IV was observed in 56.5% of cases. Patients without distant metastasis were more often female, older (>70 years) and presented as stage III with lymph node or ITM at initial diagnosis in 45.7% of cases. Melanoma located on the leg had a significantly better overall survival (OS) from time of initial diagnosis compared to non-leg localised primaries (hazard ratio [HR] = 0.61, 95% confidence interval [CI] 0.40–0.91; p = 0.017), but not from diagnosis of unresectable stage III (HR = 0.67, 95% CI 0.45–1.02; p = 0.06). Forty percent of patients received local therapy for satellite and ITM. Overall response rate (ORR) to all local first-line treatments was 38%; disease control rate (DCR) was 49%. In total, 72.3% of patients received systemic therapy for unresectable stage IIIB-D. ORR for targeted therapy (n = 19) was highest with 63.2% and DCR was 84.2% compared to an ORR of 31.4% and a DCR of 54.3% in PD-1 treated patients (n = 70). Patients receiving PD-1 and intralesional talimogene laherparepvec (n = 12) had an ORR of 41.7% and a DCR of 75%. Conclusion: Patients with unresectable ITM and without distant progression are more often female, older, and have a primary on the leg. Response to PD-1 inhibitors in this cohort was lower than expected, but further investigation is required to elucidate the biology of ITM development and the interplay with the immune system.
CRIS-Team Scopus Importer:2021-07-23
Keywords: Immune checkpoint blockade; In-transit; Intralesional therapy; Melanoma; Prognosis; Satellite; Survival; Targeted therapy

Dry Mouth under Immune Checkpoint Inhibitors: an Analysis of 29 Patients from 10 German Skin Cancer Centers - Hensen, J.; Thoms, K. M.; Kaehler, K.; Gutzmer, R.; Zimmer, L.; Zacher, M.; Alter, M.; Loquai, C.; Moreira, Alvaro; Hassel, J.; Utikal, J. (2018)
EVALuna2:34769

ECP as prognostic Marker for Melanoma - Moreira, Alvaro; Krueckel, A.; Schuler, Gerold; Utikal, J.; Heinzerling, Lucie (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-09-13

Effective anti-programmed death-1 therapy in a SUFU-mutated patient with Gorlin-Goltz syndrome - Moreira, Alvaro; Kirchberger, M. C.; Toussaint, Frédéric; Erdmann, M.; Schuler, Gerold; Heinzerling, Lucie (British Journal of Dermatology, 2018)
We present the case of a 77-year-old male patient with more than 50 basal cell carcinomas on the head and upper trunk. The patient did not respond to several lines of treatment, including surgery, imiquimod, retinoids, itraconazole and therapy with the hedgehog inhibitor vismodegib. The patient responded well to off-label therapy with the anti-programmed death-1 antibody pembrolizumab after four infusions.
EVALuna2:34414

Eosinophil-cationic protein - a novel liquid prognostic biomarker in melanoma - Krueckel, Annika; Moreira, Alvaro; Froehlich, Waltraud; Schuler, Gerold; Heinzerling, Lucie (BMC Cancer, 2019)
BackgroundThe role of eosinophils in cancer is not yet completely understood, but patients with eosinophilia show a trend towards longer survival in several types of cancer, including melanoma. However, eosinophil count at initial diagnosis of metastatic melanoma does not predict survival. Since eosinophil cationic protein (ECP) mediates anticancer effects, such as tissue remodelling and cytotoxic activity, we investigated this marker as an early prognostic marker in metastatic melanoma.MethodsSerum of 56 melanoma patients was collected at the time of diagnosis of metastatic disease. ECP levels as measured by ELISA were correlated with overall survival (OS) in patients before systemic therapy with immunotherapy or chemotherapy. Statistical analyses were performed using the Log-Rank (Mantel-Cox) test.ResultsThe median OS for patients with high serum ECP above 12.2ng/ml was 12months (n=39), compared to 28months for patients with ECP below this threshold (n=17; p=0.0642). In patients with cutaneous melanoma, excluding patients with uveal and mucosal melanoma, the survival difference was even more striking (p=0.0393). ECP's effect size on OS was observed independently of the consecutive therapy. ECP levels were not correlated with LDH levels.ConclusionECP seems to be a novel prognostic serum marker for the outcome of melanoma patients, which is independent of LDH and easy to perform in clinical practice. The striking negative prognostic value of high ECP level is unanticipated and can guide patient management.
CRIS-Team WoS Importer:2019-03-22

Eosinophil-cationic protein: A novel liquid prognostic biomarker in melanoma - Moreira, Alvaro; Krueckel, Annika; Schuler, Gerold; Heinzerling, Lucie (2018)
EVALuna2:203621

Eosinophilic count as a biomarker for prognosis of melanoma patients and its importance in the response to immunotherapy - Moreira, Alvaro; Leisgang, Waltraud; Schuler, Gerold; Heinzerling, Lucie (Immunotherapy, 2017)
AIM: The prognostic role of eosinophils in cancer has been controversial. Some entities such as gastrointestinal cancers show a better survival, while others such as Hodgkin's lymphoma a worse survival in patients with eosinophilia. Patients who exhibited an increase in eosinophils upon therapy with ipilimumab or pembrolizumab were shown to survive longer. We wanted to investigate whether eosinophilia is a prognostic marker in metastatic melanoma. METHODS: In total, 173 patients with metastatic melanoma from our data base (median age 60 years; n = 86 with immunotherapy, n = 87 without immunotherapy) were analyzed for eosinophil counts and survival over the course of 12 years. Eosinophilic count was detected by peripheral blood smear. The ethical committee had approved this retrospective study. RESULTS: Melanoma patients with eosinophilia at any point in their course of disease show a trend toward longer survival independently of their therapy. There is a statistically significant difference for the patients who survive at least 12 months (p < 0.005). In patients with checkpoint inhibitor therapy, survival was significantly prolonged in every patient with eosinophilia (p < 0.05). Furthermore, 69% of the patients treated with immunotherapy experienced at least once an eosinophilia of 5% or greater compared with 46% in the immunotherapy naive-group; for an eosinophilia of 10% values were 30 and 9%, respectively. Interestingly, in patients with more than 20% eosinophils (n = 7) survival was prolonged with a median of 35 months (range 19-60 months) as compared with 16 months (range 1-117 months). CONCLUSION: Eosinophilia is a prognostic marker in patients with metastatic melanoma.
EVALuna2:34325

Eosinophilic count as a biomarker for prognosis of melanoma patients - Moreira, Alvaro; Heinzerling, Lucie (2017)
EVALuna2:34330

Eosinophilic Fasciitis by Treatment with Checkpoint Inhibitors in metastatic Melanoma - Toussaint, Frédéric; Erdmann, M.; Moreira, Alvaro; Kirchberger, M. C.; Schuler, Gerold; Heinzerling, Lucie (2018)
EVALuna2:34779

Expression of Senescence Markers - Is Predictive for Immune Therapy with Checkpoint Inhibitors? - Moreira, Alvaro; Gross, S.; Kirchberger, M. C.; Erdmann, M.; Schuler, Gerold; Heinzerling, Lucie (2018)
EVALuna2:34778

Growing interest in hair loss - Moreira, Alvaro (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Hyponatremia and Nephritis - Rare Side Effects of Checkpoint Inhibitors in Patients with metastatic Melanoma - Mitzel-Rink, H.; Hassel, J.; Berking, C.; Gutzmer, R.; Heinzerling, Lucie; Majenka, P.; Meier, F.; Moreira, Alvaro; Terheyden, P.; Thoms, K. M.; Tietze, J.; Zimmer, L.; et al. (2018)
EVALuna2:34770

Lungs Ailment - other Comorbidity of the Psoriasis? - Moreira, Alvaro; Sticherling, Michael (2017)
EVALuna2:34355

Myositis and neuromuscular side-effects induced by immune checkpoint inhibitors - Moreira, Alvaro; Loquai, Carmen; Pfoefer, Claudia; Kaehler, Katharina C.; Knauss, Samuel; Heppt, Markus V.; Gutzmer, Ralf; Dimitriou, Florentia; Meier, Friedegund; Mitzel-Rink, Heidrun; Schuler, Gerold; Terheyden, Patrick; et al. (European Journal of Cancer, 2019)
AIM: To characterise clinical presentation, laboratory and histopathologic characteristics and assess the treatment and outcome of neuromuscular side-effects of checkpoint therapy. METHODS: The side-effect registry and the institutional database from ten skin cancer centres were queried for reports on myositis and neuromuscular side-effects induced by checkpoint inhibitors. In total, 38 patients treated with ipilimumab, tremelimumab, nivolumab and pembrolizumab for metastatic skin cancer were evaluated and characterised. RESULTS: Myositis was the most frequent neuromuscular adverse event. In 32% of cases, myositis was complicated by concomitant myocarditis. Furthermore, cases of isolated myocarditis, myasthenia gravis, polymyalgia rheumatica, radiculoneuropathy and asymptomatic creatine kinase elevation were reported. The onset of side-effects ranged from the first week of treatment to 115 weeks after the start of therapy. Most of the cases were severe (49% grade III-IV Common Terminology Criteria for Adverse Events), and there were two fatalities (5%) due to myositis and myositis with concomitant myocarditis. Only half of the cases (50%) completely resolved, whereas the rest was either ongoing or had sequelae. Steroids were given in 80% of the resolved cases and in 40% of the unresolved cases. CONCLUSION: Immune-mediated neuromuscular side-effects of checkpoint inhibitors greatly vary in presentation and differ from their idiopathic counterparts. These side-effects can be life threatening and may result in permanent sequelae. Occurrence of these side-effects must be taken into consideration for patient information, especially when considering adjuvant immunotherapy with anti-programmed cell-death protein 1 (PD-1) antibodies and monitoring, which should include regular surveillance of creatine kinase.
EVALuna2:36556

Neuromuscular Side Effects of Immune Checkpoint Inhibitors - Moreira, Alvaro; Loquai, C.; Knauss, S.; Gutzmer, R.; Dimitriou, F.; Meier, F.; Heppt, M.; Mitzel-Rink, H.; Schuler, Gerold; Terheyden, P.; Thoms, K. M.; Zimmer, L.; et al. (2018)
EVALuna2:34768

Predicting the response of uveal melanoma to immunotherapy with MRI assessments - Moreira, Alvaro; Saake, Marc; Schuler, Gerold; Heinzerling, Lucie (CANCER IMMUNOLOGY RESEARCH, 2019)
CRIS-Team WoS Importer:2021-10-18

Real world experience in low-dose ipilimumab in combination with PD-1 blockade in advanced melanoma patients - Kirchberger, Michael Constantin; Moreira, Alvaro; Erdmann, Michael; Schuler, Gerold; Heinzerling, Lucie (Oncotarget, 2018)
Dual immune-checkpoint blockade with the anti-PD-1 antibody nivolumab (1 mg/kg) and standard-dose ipilimumab (3 mg/kg) is the mainstay of immunotherapy in advanced melanoma and it is approved since 2016. However, severe side effects (grade 3/4) occur in up to 60% of the patients. Recently, clinical trials have shown similar anti-tumor activity with a more favorable toxicity profile in patients treated with low-dose ipilimumab (1 mg/kg) and standard-dose pembrolizumab (2 mg/kg). In this study we report on the real-world experience of this dosing regime in advanced melanoma patients not eligible for clinical trials. A total of 33 patients with metastatic melanoma (24 with cutaneous and 9 with uveal melanoma) were assessed, retrospectively. Brain metastases were present in 33% of the patients and lactate dehydrogenase was elevated in 70%. Overall response rates were 38% and 0% in cutaneous melanoma and uveal melanoma respectively. Median overall survival was not reached in cutaneous melanoma and was 18 months in uveal melanoma. In 18% of the patients at least one treatment-related severe adverse event was observed. Our observation that the combination of standard dose pembrolizumab and low-dose ipilimumab has a favorable toxicity profile yet anti-tumor activity comparable to the approved standard-dose combination regime in advanced patients not suitable for enrollment in clinical trials is encouraging.
EVALuna2:34415

Senescence markers: Predictive for response to checkpoint inhibitors - Moreira, Alvaro; Gross, Stefanie; Kirchberger, Michael Constantin; Erdmann, Michael; Schuler, Gerold; Heinzerling, Lucie (International Journal of Cancer, 2019)
Recent studies suggest that the age-related remodeling of the immune system, known as immunosenescence, could impact the efficacy of immune checkpoint inhibitors in leukemia or nonsmall cell lung cancer. We investigated whether senescence markers can predict response to checkpoint inhibitor therapy in melanoma patients. The peripheral blood of patients with newly diagnosed, untreated metastatic melanoma was analyzed by flow cytometry to correlate the frequency of senescence markers with clinical response as measured by RECIST after 12 weeks of treatment with immune checkpoint inhibitors. The loss of surface markers CD27 and CD28 or the expression of Tim-3 and CD57 on T cells was associated with resistance to checkpoint inhibitor blockade, presenting these phenotypes as possible predictive biomarkers for checkpoint inhibitor therapy. Immunosenescence seems to impact on the response to checkpoint inhibitor therapy in melanoma patients. Thus, lymphocyte phenotyping for senescence markers, with the introduction of immunosenescence panels, could be predictive for checkpoint inhibitor response.
CRIS-Team Scopus Importer:2019-05-21
Keywords: biomarker; immune checkpoint inhibitors; immunosenescence; melanoma

Skin symptoms as diagnostic clue for autoinflammatory diseases - Moreira, Alvaro; Torres, Barbara; Peruzzo, Juliano; Mota, Alberto; Eyerich, Kilian; Ring, Johannes (Anais Brasileiros De Dermatologia, 2017)
Autoinflammatory disorders are immune-mediated diseases with increased production of inflammatory cytokines and absence of detectable autoantibodies. They course with recurrent episodes of systemic inflammation and fever is the most common symptom. Cutaneous manifestations are prevalent and important to diagnosis and early treatment of the syndromes. The purpose of this review is to emphasize to dermatologists the skin symptoms present in these syndromes in order to provide their early diagnosis.
EVALuna2:35416

Step-by-step Improvement of mRNA-electroporated dendritic Cells in a Phase I / II Clinical Study in cutaneous Melanoma Patients: better Survival correlates with a higher Immunoscore and increased Expression of PEBP1 in the Blood - Dörrie, Jan; Schaft, Niels; Gross, S.; Ostalecki, Christian; Eberhardt, Martin; Vera-Gonzales, J.; Uslu, Ugur; Moreira, Alvaro; Koch, Elias; Kummer, Mirko; Erdmann, M.; Schliep, S.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

Vaccination with dendritic Cells for metastasized Uveal Melanoma: immunological and clinical Responses - Moreira, Alvaro; Gross, S.; Uslu, Ugur; Dörrie, Jan; Kummer, Mirko; Schliep, S.; Sponagl, F.; Lischer, Christopher; Erdmann, M.; Heinzerling, Lucie; Schuler, Gerold; Schuler-Thurner, Beatrice (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-09-13